1998
DOI: 10.1046/j.1365-313x.1998.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence for 5′→3′ exoribonuclease degradation of an unstable chloroplast mRNA

Abstract: SummaryThe acetate-requiring Chlamydomonas reinhardtii nuclear mutant F16 harbors the mutation mcd1-1 and fails to accumulate the cytochrome b6/f complex. The primary defect of mcd1-1 was determined to be the instability of petD mRNA, which encodes subunit IV of the complex. Chimeric reporter genes introduced by chloroplast transformation demonstrated that the determinant of petD mRNA instability in the mcd1-1 background is located in the 5Ј untranslated region (UTR). However, when this 5Ј UTR was present down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 68 publications
4
95
1
Order By: Relevance
“…Although we had to begin with a relatively unstable (atpB⌬26) mRNA to test added 3Ј-UTR sequences, the results clearly showed a destabilizing effect of poly(A), which was expected on the basis of previous in vitro results, and a probable stimulatory effect of poly(U), which was unexpected. Although we did not measure transcription rates here, we have shown (21,26,32) that 3Ј-UTR manipulations do not affect the atpB or petD promoters. Thus, the absence or decrease in RNA levels must be caused by instability.…”
Section: Discussionmentioning
confidence: 91%
“…Although we had to begin with a relatively unstable (atpB⌬26) mRNA to test added 3Ј-UTR sequences, the results clearly showed a destabilizing effect of poly(A), which was expected on the basis of previous in vitro results, and a probable stimulatory effect of poly(U), which was unexpected. Although we did not measure transcription rates here, we have shown (21,26,32) that 3Ј-UTR manipulations do not affect the atpB or petD promoters. Thus, the absence or decrease in RNA levels must be caused by instability.…”
Section: Discussionmentioning
confidence: 91%
“…2 were not due to a peculiarity of the reporter gene chosen, certain constructs were replicated using the aadA coding region instead of uidA. aadA is a commonly used selectable marker gene in Chlamydomonas chloroplasts and has also been used to study RNA cis elements (8,30). Fig.…”
Section: Fig 2 Sequence Requirements For Ecs-originated Downstream mentioning
confidence: 99%
“…The region spanning from 10 -89 nt downstream of the atpB stop codon contains an IR sequence predicted to form an AU-rich stem-loop structure, and the mature 3Ј end is found 3-4 nt downstream of the IR (12, 13). Deletions that destabilize this structure cause RNA instability (12); however the sequence can be functionally replaced by an IR from spinach chloroplasts (13) or by a polyguanosine tract, which forms a tertiary structure impervious to either 5Ј 3 3Ј or 3Ј 3 5Ј exonucleases (8,14).Both in vitro and in vivo approaches have shown that chloroplast IR sequences do not efficiently terminate transcription, and those tested include Chlamydomonas atpB (13,15). This implies that post-transcriptional 3Ј end maturation is required.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, analysis of chloroplast reporter gene constructs revealed that, in both C. reinhardtii and tobacco, rbcL transcripts are stabilized via elements within their 5¢ regions in vivo (Salvador 1993;Shiina et al 1998). The same applies to 5¢UTRs of psbD, petD and psbB transcripts in C. reinhardtii, which were shown to contain the target sites for nucleus-encoded factors involved in the gene-specific stabilization of the corresponding mRNAs (Nickelsen et al 1994;Drager et al 1998;Vaistij et al 2000a). For psbD and petD RNAs, site-directed mutagenesis enabled the precise localization of distinct RNA elements mediating RNA stabilization (Higgs et al 1999;Nickelsen et al 1999).…”
Section: Rbps Interacting With 5¢utrsmentioning
confidence: 92%